PENGARUH PERLAKUAN SUHU DAN BEBERAPA GENOTIPE TERHADAP VIABILITAS DAN VIGOR BENIH KUBIS BUNGA (BRASSICA OLERACEA VAR. BOTRYTIS L.) PADA DATARAN RENDAH - Lestari Maulana; Elia Azizah; Winda Rianti; Sugiarto Sugiarto (MEDIAGRO, 2021)
The aim of this study was to obtain the best temperature on several genotypes so as to increase the best viability and vigour of cauliflower seeds in the lowlands. The research was conducted at the Laboratory Agronomy, OPT and Soil Biotechnology Faculty of Agriculture, Singaperbangsa Karawang University. The research method used was an experimental method with a two-factor completely randomized design (CRD). The first factor is temperature which consists of room temperature without air conditioning (P0), air-conditioned room temperature (P1) and refrigerator temperature (P2). The second factor is genotypes consisting of Viola (B1), Tegar 45 (B2), Snow Waltz (B3), Jayanti (B4), Giga (B5), Snow White (B6), Diamond (B7), Orient (B8). , Roo So 45 (B9), Forum (B10), Bima (B11), F1 Hybrid (B12) and Arjuna (B13). Each treatment was repeated 2 times so that 78 experiments were obtained and 2 times planting (before and after storage). The results of the pre-storage experiment showed that there was no interaction between temperature treatment and several genotypes, but in the post-storage experiment, there were an interaction with the parameters of germination, concurrency of growth, vigor index and maximum growth potential, while for parameters of moisture content, normal germinated dry weight and length of sprouts. indicates there is no interaction. The best treatment was room temperature without AC genotype Roo So 45 (P0B9). Keywords: Cabbage flower, genotype, temperature, , viability, vigour.